UPAYA PENANAMAN DAN PEMBENTUKAN KARAKTER SISWA MELALUI KEGIATAN PERMAINAN TRADISIONAL MARJALENGKAT - Novi Astika Rambe; Daulat Saragi (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The Indonesian nation has many cultures and is so inherent and even inseparable in everyday life, one of which is traditional games. Traditional games are one of the relevant and harmonious cultures to be applied to children, because traditional games themselves have many character values that can develop the character of school children. In addition, traditional games are able to provide positive things that the digital world cannot provide, therefore traditional games are crucial in instilling student character values which are useful in students' daily lives. This study aims to instil character values through marjalengkat games. This study is a qualitative study with a descriptive nature and this study will be conducted at SD Negeri 165733 Tebing Tinggi. Data were obtained through direct observation, interviews, and note-taking. The results of the study show that the character values that can be instilled through traditional marjalengkat games are religion, nationalism, independence, mutual cooperation and integrity.